Accepting the newcomer: Do information and voting shape cooperation within groups? - Alexandra Baier; Natalie Struwe (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
We study cooperation in an environment where public good providers face the decision to accept a newcomer to their group. A bottom-up process for accepting new members to social groups reveals individual preferences to include newcomers. Alternatively, inclusion can be decided in a top-down process by a third party. We present data from an online public good experiment, varying first whether inclusion of a newcomer is exogenously imposed through a random draw or endogenously decided on by the group members through a majority voting rule. Secondly, we target uncertainty about the behavior of the newcomer by providing feedback information on previous prosocial behavior from a dictator-to-charity task of the newcomer. The results demonstrate a high general willingness to include newcomers, with the voting process resulting in significantly higher inclusion rates compared to the exogenous process. The prosocial information neither affects aggregate inclusion nor aggregate cooperation outcomes significantly. Providing information on prior prosocialty, however, constitutes a significant determinant for individual behavior: it directly affects the likelihood of group members to vote for inclusion, as well as influencing expectations on future cooperativeness of the newcomer.
Keywords: C72; C92; D64; H41; 330; endogenous group formation; inclusion; public good; charitable giving; cooperation